The impact of socioeconomic status on HPV infection among young Brazilians in a nationwide multicenter study - Kops, Natália L. (Prev Med Rep, 2021)
The aim of this study is to evaluate genital human papillomavirus (HPV) infection according to socioeconomic categories in Brazil. This cross-sectional, nationwide study included 7,694 sexually active women and men aged 16–25 years. Individuals of all socioeconomic groups in all 26 Brazilian capitals and the Federal District were enrolled through public primary care units between September 2016 and November 2017. All participants answered a standardized interview administered by trained primary care health professionals. Socioeconomic class was analyzed using a pricing classification system for the Brazilian public that divides the market exclusively in terms of economic class based on the ownership of assets and the education level. Cervical samples were obtained using a Digene® HC2 DNA Collection, and penile/scrotum samples were obtained using a wet Dacron swab. HPV typing (overall and high-risk) was performed in a central lab. Of the 7,694 participants (47.85% women), 17.92% belonged to class A-B, 56.08% to class C, and 26.00% to class D-E. The prevalence of overall HPV was similar among the social classes: 51.16% for classes A-B, 53.39% for class C, and 55.47% for classes D-E (P = 0.479). Similar results were found for high-risk HPV. After adjustments, the presence of HPV in individuals with a brown skin color belonging to classes A-B was 57.00% higher [prevalence ratio 1.57 (95%: 1.23, 2.01)] than that in whites and had no impact on the other social classes. In conclusion, HPV infection affects all socioeconomic classes in Brazil, evidencing the importance of offering the HPV vaccine to the entire population.